1998
DOI: 10.1083/jcb.143.5.1249
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Rho-associated Kinase in Cytokinesis; Mutations in Rho-associated Kinase Phosphorylation Sites Impair Cytokinetic Segregation of Glial Filaments

Abstract: Rho-associated kinase (Rho-kinase), which is activated by the small GTPase Rho, regulates formation of stress fibers and focal adhesions, myosin fiber organization, and neurite retraction through the phosphorylation of cytoskeletal proteins, including myosin light chain, the ERM family proteins (ezrin, radixin, and moesin) and adducin. Rho-kinase was found to phosphorylate a type III intermediate filament (IF) protein, glial fibrillary acidic protein (GFAP), exclusively at the cleavage furrow during cytokinesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
152
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 155 publications
(158 citation statements)
references
References 39 publications
3
152
2
Order By: Relevance
“…Here, we demonstrated that Rho-kinase diphosphorylates MRLC and colocalizes with the diphosphorylated MRLC at the cleavage furrow in dividing HeLa cells. Other substrates phosphorylated by Rho-kinase have been reported to accumulate at the cleavage furrow in dividing non-muscle cells (Yasui et al, 1998;Kawano et al, 1999). Recently, Kosako et al (2000) reported that Rho-kinase is involved in cytokinesis through the monophosphorylation of MRLC and not ERM at the cleavage furrow.…”
Section: Roles Of Diphosphorylated Mrlc Induced By Rho-kinasementioning
confidence: 99%
See 1 more Smart Citation
“…Here, we demonstrated that Rho-kinase diphosphorylates MRLC and colocalizes with the diphosphorylated MRLC at the cleavage furrow in dividing HeLa cells. Other substrates phosphorylated by Rho-kinase have been reported to accumulate at the cleavage furrow in dividing non-muscle cells (Yasui et al, 1998;Kawano et al, 1999). Recently, Kosako et al (2000) reported that Rho-kinase is involved in cytokinesis through the monophosphorylation of MRLC and not ERM at the cleavage furrow.…”
Section: Roles Of Diphosphorylated Mrlc Induced By Rho-kinasementioning
confidence: 99%
“…These suggest that the regulation of actin cytoskeleton through MRLC diphosphorylation may be essential for tumor cell invasion. Yasui et al (1998) reported that expression of the dominant-negative form of Rho-kinase inhibited cytokinesis and increased in the multi-nuclei cells, suggesting that Rho-kinase plays an important role in cytokinesis. Here, we demonstrated that Rho-kinase diphosphorylates MRLC and colocalizes with the diphosphorylated MRLC at the cleavage furrow in dividing HeLa cells.…”
Section: Roles Of Diphosphorylated Mrlc Induced By Rho-kinasementioning
confidence: 99%
“…Twenty-four or 48 h after transfection, the cells were fixed for immunocytochemical studies. In some experiments, 48 h after transfection, the mitotic cells were prepared as described (17) and incubated for 3 h to allow for cell cycle progression. Intermediate filament (IF) bridge formation and multinuclear cells were analyzed immunocytochemically.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, we found that the expression of mutant GFAP, where the Rho-kinase phosphorylation sites were substituted to alanine residues, impaired cytokinetic segregation of GFAP ®laments, resulting in the formation of an unusually long bridge-like structure between the unseparated daughter cells (Yasui et al, 1998). These observations suggest that the phosphorylation-dependent disassembly of intermediate ®laments is required for proper execution and completion of cytokinesis.…”
mentioning
confidence: 96%